DINAMIKA PERMAINAN MONOPOLI DALAM PERKEMBANGAN KOGNITIF SISWA-SISWI DI PAUD TK ANAK CERIA SURABAYA - Dwi Nata, Lola; Salsabila, Annisa; Talitha, Adeline; Untsal Asad, Amiroh; Sasi Kirana, Rhein (Lafadz Jaya Publisher, 2025)
Monopoly games are increasingly neglected along with the development of increasingly sophisticated gadgets. This research aims to stimulate the cognitive aspects of preschool children to be able to develop and train their abilities by using symbols, such as words, pictures, and ideas so that they can present a concept. This research is based on Piaget's cognitive theory, especially in the preoperational stage. This study used a qualitative approach, using participatory observation techniques and informal interviews involving three subjects and using a review of previous literature to compare the results of the study. The results stated that the subjects were able to present the media in the Monopoly game using language, number patterns, pictures, colors, train executive functions, and train children to organize strategies in solving a simple problem. The results of this study are also supported by giving pre-test and post test during the implementation of stimulation activities. Future research can use other simple media to train cognitive aspects of pre-school children, using quantitative methods so that other aspects outside this study can be measured and more systematic.